Transcriptomic and Metabolomic Analyses Reveal a Potential Mechanism to Improve Soybean Resistance to Anthracnose - Zhu, Longming; Yang, Qinghua; Yu, Xiaomin; Fu, Xujun; Jin, Hangxia; Yuan, Fengjie (Frontiers in Plant Science, 2022)
Anthracnose, caused by Colletotrichum truncatum, leads to large-scale losses both in quality and yield in soybean production. Limited information is available regarding the molecular mechanisms of resistance in the soybean to anthracnose. We conducted a transcriptomic and targeted metabolomic analysis of pods from two soybean lines, ‘Zhechun No. 3’ (ZC3) and ZC-2, in response to C. truncatum infection. Several factors that contributed to the enhanced resistance of ZC-2 to anthracnose compared with that of ZC3, including signal transduction (JA, AUX, MAPK, and Ca2+ signaling), transcription factors (WRKY and bHLH), resistance genes (PTI1, RPP13, RGA2, RPS6, ULP2B), pathogenesis-related genes (chitinase and PR14), and terpenoid metabolism were revealed. Targeted metabolomic analysis revealed that terpenoid metabolism was more timely and more intense in response to C. truncatum infection in ZC-2 than that in ZC3. Meanwhile, in vitro antifungal and induce resistance test comfirmed that JA , AUX signaling and terpenoids were play important roles in soybean resistance to anthracnose. This research is the first attempt to explore the molecular mechanisms of soybean resistance to anthracnose, which is important for in-depth analysis of molecular resistance mechanisms, discovery of resistance genes, and accelerating the breeding of resistant soybean cultivars.